2000
DOI: 10.1016/s0735-1097(99)00525-2
|View full text |Cite
|
Sign up to set email alerts
|

The evolving role of statins in the management of atherosclerosis

Abstract: Significant advances in the management of cardiovascular disease have been made possible by the development of 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase inhibitors--"statins." Initial studies explored the impact of statin therapy on coronary artery disease (CAD) progression and regression. Although the angiographic changes were small, associated clinical responses appeared significant. Subsequent large prospective placebo-controlled clinical trials with statins demonstrated benefit in the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
314
1
19

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(344 citation statements)
references
References 86 publications
10
314
1
19
Order By: Relevance
“…They are the most efficient agents for reducing plasma cholesterol, being also appreciated for their good tolerance. Angiographic studies have demonstrated that these compounds reduce the progression and may induce the regression of atherosclerotic lesion in cardiovascular vessels, which could lead to a significant decreases of cardiovascular morbidity and mortality [15]. Statins have been shown to inhibit hepatic production of apoA-IV apoB, apoCIII and apoE-containing lipoproteins both in vitro and in vivo [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…They are the most efficient agents for reducing plasma cholesterol, being also appreciated for their good tolerance. Angiographic studies have demonstrated that these compounds reduce the progression and may induce the regression of atherosclerotic lesion in cardiovascular vessels, which could lead to a significant decreases of cardiovascular morbidity and mortality [15]. Statins have been shown to inhibit hepatic production of apoA-IV apoB, apoCIII and apoE-containing lipoproteins both in vitro and in vivo [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Data from clinical trials have demonstrated that statin treatment appears to be the most effective and well-tolerated means of lowering cholesterol levels, [1][2][3] but it is also clear that large interindividual variations in plasma cholesterol response are common and explained, in part, by genetic factors that affect drug pharmacodynamics and/or pharmacokinetics. In recent years, one of the focus of genetic investigation in cardiology has been to identify the genetic factors associated with variable response to statin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…CETP transfers cholesteryl esters associated with HDL to triglyceride-rich lipoproteins, facilitating the clearance of cholesteryl esters from plasma. 1 Although the potential contribution of CETP to reverse cholesterol transport suggests an antiatherogenic mode of action, knowledge of the physiologic role of CETP in lipoprotein metabolism remains incomplete. The overall effect of CETP on atherogenesis may vary depending on both metabolic context and molecular variation in the CETP gene.…”
Section: Introductionmentioning
confidence: 99%